2013
DOI: 10.1016/j.medengphy.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia act as mechanosensors during bone healing around an implant

Abstract: The primary cilium is an organelle that senses cues in a cell’s local environment. Some of these cues constitute molecular signals; here, we investigate the extent to which primary cilia can also sense mechanical stimuli. We used a conditional approach to delete Kif3a in pre-osteoblasts and then employed a motion device that generated a spatial distribution of strain around an intra-osseous implant positioned in the mouse tibia. We correlated interfacial strain fields with cell behaviors ranging from prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…The surgical procedure, the osseointegration response, and the molecular and cellular characteristics of this process have been documented elsewhere [6,11,14,15,17,26,27]. Here, we show that new bone, originating from the tibial marrow cavity, is first evident on post-surgical day 5 (Supplemental Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The surgical procedure, the osseointegration response, and the molecular and cellular characteristics of this process have been documented elsewhere [6,11,14,15,17,26,27]. Here, we show that new bone, originating from the tibial marrow cavity, is first evident on post-surgical day 5 (Supplemental Fig.…”
Section: Resultssupporting
confidence: 70%
“…Using this information we have identified principal strains in the 10–20% range to stimulate osseointegration [13,14]. Genetic mouse models have been particularly helpful in identifying key variables that influence osseointegration; namely, we demonstrated that early excessive micromotion can cause fibrous encapsulation [15] and the elimination of mechanically sensitive cellular appendages such as primary cilia can obliterate the strain-induced bone formation [16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Leucht et al utilized Col1α1-Cre and Kif3a fl/fl mice to generate conditional knockout of Kif3a in osteoblasts and investigate the role of primary cilia in bone repair [22,23]. No skeletal abnormalities or aberrations in skeletal patterning were detected in embryos, pups or adult mice.…”
Section: Proposed Mechanosensory Roles Of Primary Cilia In Osteocytesmentioning
confidence: 99%
“…Deletion of Kif3a in osteoblasts/osteocytes impairs responses to load-induced bone formation, fluid flow shear stress, and strain fields caused by implant displacement, suggesting that primary cilia play an essential role in bone remodeling. (25)(26)(27) However, the role of IFT proteins in regulating fracture healing has not been investigated. The purpose of this study is to investigate the role of IFT80 in fracture healing, focusing on how it affects chondrocytes.…”
Section: Introductionmentioning
confidence: 99%